Initial and hourly headloss modelling on a tertiary nitrifying wastewater biofiltration plant. Issue 10 (18th May 2016) - Bernier, Jean; Rocher, Vincent; Lessard, Paul
ABSTRACT: The headloss prediction capability of a wastewater biofiltration model is evaluated on data from a full-scale tertiary nitrifying biofilter unit located in the Paris conurbation (Achères, France; 6, 000, 000 population equivalent). The model has been previously calibrated on nutrient conversion and TSS filtration observations. In this paper the mass of extracted biofilm during biofilter backwash and the headloss value at the start of an operation cycle are first calibrated on sludge production estimations and relative pressure measurements over the year 2009. The calibrated model is then used on two one-month periods in 2012 for which hourly headloss measurements were acquired. The observed trends are correctly predicted for 2009 but the model exhibits some heavy daily variation that is not found in measurements. Hourly predictions stay close to observations, although the model error rises slightly when the headloss does not vary much. The global model shows that both nutrient conversion and headloss build-up can be reasonably well predicted at the same time on a full-scale plant.